Batman the killing joke - Faust, Christa; Phillips, Gary 1955- (Batman novel, 2018)
"Faced with overwhelming poverty and a pregnant wife, a tragic, struggling comedian is forced to turn to crime. In his first heist, he is immersed in toxic chemicals that disfigure him bizarrely, driving him mad and thus giving birth to The Joker. For years, the Clown Prince of Crime has been caught in a dance of violence with his greatest nemesis, the Batman. Escaping Arkham Asylum, he plots his most lethal caper. This will be the ultimate punch line... his KILLING JOKE."